2013
DOI: 10.1016/j.jare.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Solar quiet day ionospheric source current in the West African region

Abstract: The Solar Quiet (Sq) day source current were calculated using the magnetic data obtained from a chain of 10 magnetotelluric stations installed in the African sector during the French participation in the International Equatorial Electrojet Year (IEEY) experiment in Africa. The components of geomagnetic field recorded at the stations from January–December in 1993 during the experiment were separated into the source and (induced) components of Sq using Spherical Harmonics Analysis (SHA) method. The range of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
1
2
2
Order By: Relevance
“…This night variation is in line with the earlier works of [14-16, 21, 22, 30-32]. Obiekezie and Okeke [16] attributed the observed nighttime variations to currents flowing in the magnetosphere (such as the ring currents) in which most of it filter into the ionosphere at night even during magnetic quiet periods.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This night variation is in line with the earlier works of [14-16, 21, 22, 30-32]. Obiekezie and Okeke [16] attributed the observed nighttime variations to currents flowing in the magnetosphere (such as the ring currents) in which most of it filter into the ionosphere at night even during magnetic quiet periods.…”
Section: Resultssupporting
confidence: 91%
“…Hasegawa [8] examined the day-to-day changes of the quiet day variation and the ionospheric current systems for the second polar year and suggested that some or all the dayto-day variabilities in solar quiet daily variation (Sq) are due to variability in the positions of the foci of the ionospheric current systems rather than changes in the distribution of ionization and conductivity. Studies conducted by [9][10][11][12][13][14][15][16] clearly showed that the variability of Sq occurred at all hours of the day.…”
Section: Introductionmentioning
confidence: 99%
“…This is found to be in agreement with Campbell et al (1993) who found the solsticial currents to be higher than the equinoctial currents. It also is contrary to the works of Obiekezie and Okeke (2013) that earlier observed their maximum peak in the month of March within the West Africa region. The Sq generation is affected generally by the transport of the ionization and the solar ionization at E region altitudes in mid and low latitude regions.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed current patterns are the same throughout the stations and quite opposite to the patterns observed by Obiekezie and Okeke (2010). This could have arisen from the fact that Obiekezie and Okeke (2010) worked on the western African region around the dip equator whereas the present study was carried out within the Southern African region which has different geological properties.…”
Section: Discussioncontrasting
confidence: 63%
“…There are different viewpoints on the issue of day‐to‐day variability in the solar quiet daily variation ( S q ). Obiekezie and Okeke () proposed that this day‐to‐day variability can be attributed to variabilities of the ionospheric process and physical structures, such as conductivity and wind structures. However, Hasegawa (1950) suggested that the day‐to‐day variability in S q is due to variability in the positions of the foci of the ionospheric current systems rather than changes in the distribution of ionization and conductivity.…”
Section: Discussionmentioning
confidence: 99%